2011
DOI: 10.1136/thx.2011.158956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urbanisation on asthma, allergy and airways inflammation in a developing country setting

Abstract: Background Asthma is a growing public health problem in developing countries. However, few studies have studied the role of urbanisation in this phenomenon. It was hypothesised that children living in a peri-urban setting in Peru have higher rates of asthma and allergy than rural counterparts. Methods 1441 adolescents aged 13–15 years were enrolled from two settings: a peri-urban shanty town in Lima (n=725) and 23 rural villages in Tumbes (n=716). Participants filled in questionnaires on asthma and allergy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 33 publications
10
82
2
3
Order By: Relevance
“…The Global Lung Function Initiative equations were used to calculate FEV1 predicted and FVC predicted and the results showed that these measures were all higher in Shibin El-Kom than Cairo. These findings confirm previous studies that reported differences in pulmonary function between urban and rural areas (8,19), which could indicate sub-clinical airway narrowing and slower pulmonary growth rate (3). The decrease in FVC and FEV1 was likely due to decrease in lung tissue elasticity and an increase in big airway resistance, although obstructions in small airways can also decrease FEV1 (20).…”
Section: Discussionsupporting
confidence: 92%
“…The Global Lung Function Initiative equations were used to calculate FEV1 predicted and FVC predicted and the results showed that these measures were all higher in Shibin El-Kom than Cairo. These findings confirm previous studies that reported differences in pulmonary function between urban and rural areas (8,19), which could indicate sub-clinical airway narrowing and slower pulmonary growth rate (3). The decrease in FVC and FEV1 was likely due to decrease in lung tissue elasticity and an increase in big airway resistance, although obstructions in small airways can also decrease FEV1 (20).…”
Section: Discussionsupporting
confidence: 92%
“…Atopic eczema has also been shown to be an increasing problem in urban Nigeria [21]. The peri-urban environment of Lima was associated with 2.6-fold greater odds (95% CI: 1.3-5.3) of allergic disease [22]. In Wuhan, close proximity to a business zone, highway, or industrial area was a risk factor for eczema symptoms, with odds ratios of 1.4-2.8.…”
Section: Discussionmentioning
confidence: 92%
“…Scott et al [18] reported a positive correlation between FeNO and the number of positive skin prick tests in a cohort of asthmatics. Previous studies have also correlated aeroallergen sensitization with FeNO levels in atopic children [7,13,16,19,20]. These findings underscore the relevance of evaluating allergen sensitization status when FeNO is used as a biomarker in the diagnosis and monitoring of asthma [18].…”
Section: Introductionmentioning
confidence: 57%
“…For these reasons, FeNO has been recently recommended as a clinical endpoint for the characterization of study populations, in clinical trials and observational studies [10]. Recent studies, however, have reported high levels of FeNO even in well-controlled asthma [1,6,11], indicating that other factors may play a role in the determination of FeNO levels [12][13][14][15]. One potential factor that could explain variability in FeNO levels is atopic status.…”
Section: Introductionmentioning
confidence: 99%